2020
DOI: 10.3390/microorganisms8030444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance, Virulence Genes and Genetic Diversity of Salmonella Isolated from Retail Duck Meat in Southern China

Abstract: Salmonella is an important cause of foodborne diseases. This study was undertaken to investigate the prevalence, serotype distribution, antimicrobial resistance, virulence genes, and genetic diversity of Salmonella isolates recovered from fresh duck meat obtained from retail markets in Southern China. In total, 365 samples of fresh duck meat were collected from retail markets in six different cities of Guangdong Province between May 2017 and April 2019. High levels of Salmonella contamination were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
5
30
0
Order By: Relevance
“…Tennessee, and S . Cerro were also commonly recovered from poultry-based products and humans in China (Bai et al, 2015 ; Chen et al, 2020 ; Yang et al, 2020 ). These reports provide strong evidence about the increasing prevalence of S .…”
Section: Discussionmentioning
confidence: 99%
“…Tennessee, and S . Cerro were also commonly recovered from poultry-based products and humans in China (Bai et al, 2015 ; Chen et al, 2020 ; Yang et al, 2020 ). These reports provide strong evidence about the increasing prevalence of S .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, high rates of Salmonella contamination in retail meats such as pork, beef, mutton, and duck meat have been reported in several places in China. A high prevalence of Salmonella contamination has been observed in chicken (63.6%), pork (73.1%), and duck meat (41.4%) in Guangdong, China ( Zhang L. et al, 2018 ; Chen et al, 2020 ). In a study in which a total of 807 retail meat samples were collected from most provincial capitals in China between July 2011 and June 2016, 19.7% of the samples tested positive for Salmonella .…”
Section: Introductionmentioning
confidence: 99%
“…Variable numbers of predominant serotypes have been documented in chickens sampled from cottage processors in the country, for example, Rodrigo, Adesiyun, Asgarali, and Swanston (2006) reported that the frequently isolated serotypes from carcass drips, liver, and heart and gizzard sample were serotypes Kiambu (53.0%) and Kentucky (38.5%) while in a recent study on carcass swabs, the predominant serotypes detected were Javiana (30.9%) and Kentucky (23.5%) (Khan et al., 2018). Diversity of predominant serotypes of Salmonella recovered in chickens sampled from the “wet market” have been reported in other countries and are known to reflect the prevalence of the pathogen on poultry farms and cross contamination during slaughter and processing (Chen et al., 2020; Vinueza‐Burgos, Baquero, Medina, & De Zutter, 2019). Contributors to the varying frequencies of detected serotypes include the fact that conventional subtyping of Salmonella strains is known to provide frequent misclassification, it has very poor subtype discrimination (Petersen et al, 2004), the process could take 2–17 days (Bopp et al., 2016), among other limitations (Tang et al., 2019).…”
Section: Discussionmentioning
confidence: 93%